2020
DOI: 10.1002/chem.202000462
|View full text |Cite
|
Sign up to set email alerts
|

Two Orthogonal Halogen‐Bonding Interactions Directed 2D Crystalline Supramolecular J‐Dimer Lamellae

Abstract: Dye assemblies exhibit fascinating properties and performances, both of which depend critically on the mutual packing arrangement of dyes and on the supramolecular architecture. Herein, we engineered, for the first time, an intriguing chlorosome‐mimetic 2D crystalline J‐dimer lamellar structure based on halogenated dyes in aqueous media by employing two distinct orthogonal halogen‐bonding (XB) interactions. As the only building motif, antiparallel J‐dimer was formed and stabilized by single π‐stacking and dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 76 publications
1
35
0
Order By: Relevance
“…The two chlorine atoms substituted at the 2,6‐positions of BODIPY are expected to provide XB interactions to drive and stabilize the dye aggregation with highly ordered molecular arrangements in water. [ 16 ] Notably, a bulky substituent was anchored at the meso ‐position of the BODIPY component of BD‐Gd with the aim of preventing close face‐to‐face H‐stacking while facilitating J‐stacking of BODIPY components. [ 2b,20 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two chlorine atoms substituted at the 2,6‐positions of BODIPY are expected to provide XB interactions to drive and stabilize the dye aggregation with highly ordered molecular arrangements in water. [ 16 ] Notably, a bulky substituent was anchored at the meso ‐position of the BODIPY component of BD‐Gd with the aim of preventing close face‐to‐face H‐stacking while facilitating J‐stacking of BODIPY components. [ 2b,20 ]…”
Section: Resultsmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) and atomic force microscopy (AFM) results revealed a morphology of random nanosheet material approximately 3.5 nm thick (Figure 2d,e). Compared with the thermodynamically stable self‐assembly of chlorinated BODIPY analogue (BDP‐Cl) driven by highly directional XB interactions (Figure 2b), [ 16 ] the absorption band and morphology of the BD‐Gd nanosheet indicate that it should be a kinetically controlled nano‐assembly. [ 8 ] As expected, after heat treatment (see Supporting Information), a ribbonlike nano‐lamella with a thickness of ≈6.6 nm and a length in micrometer scale was observed by TEM and AFM (Figure 2f,g), which is almost identical to that of the crystalline self‐assembly of BDP‐Cl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, two absorption bands were observed between 510–530 and 580–600 nm for all B1‐B4 and B4‐II , unlike in their solution spectra. The band at 510–530 nm is attributed to the S 0 –S 1 transition, whereas the second absorption bands at 580–600 nm are possibly due to some aggregation involving J‐aggregation with panchromatic property [30] . In addition, two polymorph structures B4 and B4‐II exhibit different absorption profiles as seen in Figure 7.…”
Section: Figurementioning
confidence: 97%
“…However, the design of efficient supramolecular architectures with highly complex structures, such as BODIPY, presents a great challenge and requires comprehensive knowledge of noncovalent interactions. Recently, a few studies have reported observation of the XB interaction in their BODIPY structures [28–31] …”
Section: Figurementioning
confidence: 99%